Empowering Sustainable Practices: Enhancing Food Management and Waste Reduction in an Agricultural Community - Atikha Sidhi Cahyana; Inggit Marodiyah; Intan Rohma Nurmalasari (Indonesian Journal of Cultural and Community Development, 2023)
This study addresses knowledge gaps in a rural agricultural community, exemplified by Kajartengguli Village, where low education levels have influenced conventional waste disposal methods. With 49% of residents lacking formal schooling, and only 6% holding degrees, unsustainable waste management practices persist, including burning waste without considering consequences. The initiative, conducted on February 8, 2023, engaged PKK women from Kajartengguli Village, Prambon District, Sidoarjo Regency, in disseminating effective food preparation and preservation techniques. By appropriately storing ingredients such as vegetables, fish, and seasonings, the community aimed to extend their shelf life. Positive reception of the training has sparked enthusiasm among Kajartengguli women, showcasing potential for reduced food waste and enhanced sustainability practices in similar contexts. Highlight: Educational Disparities: Addressing the influence of low education levels on conventional waste disposal practices in a rural agricultural community. Sustainable Waste Management: Highlighting persisting unsustainable waste disposal practices, including unconsidered burning, and the need for effective interventions. Empowering Change: Demonstrating the impact of engaging PKK women in disseminating improved food preparation and preservation techniques, fostering enthusiasm for enhanced sustainability and reduced food waste within the community. Keyword: Knowledge Gaps, Rural Community, Waste Management, Food Preparation, Sustainability